2017
DOI: 10.1017/s1460396917000115
|View full text |Cite
|
Sign up to set email alerts
|

The use of 3D printing within radiation therapy to improve bolus conformity: a literature review

Abstract: Background and purposeIn radiotherapy (RT) bolus material is used to increase skin dose and eliminate the ‘skin-sparing’ effect. Bolus fabrication is limited to the expertise of the practitioner and is time and resource intensive for both patients and staff to construct bolus. In addition, prefabricated bolus does not always conform to irregular surfaces resulting in variations to dose distribution at the skin surface. The purpose of this paper is to ascertain whether it is feasible to improve bolus conformity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 6 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…The process of nose bolus manufactured from wax is labour intensive. Volumetric and dosimetric accuracy is limited by the experience and skill of the radiation therapist (RT) or mould room technician, as well as variations inherent to the manual nature of the process, including air cavity flaws and imperfect contact with the patient’s skin . Three‐dimensional printed bolus offers a unique solution to eliminate any physical variation between the bolus planned within a treatment planning system (TPS) and what would otherwise be constructed by a skilled hand, thereby limiting the potential for a difference between the planned and delivered radiation dose …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of nose bolus manufactured from wax is labour intensive. Volumetric and dosimetric accuracy is limited by the experience and skill of the radiation therapist (RT) or mould room technician, as well as variations inherent to the manual nature of the process, including air cavity flaws and imperfect contact with the patient’s skin . Three‐dimensional printed bolus offers a unique solution to eliminate any physical variation between the bolus planned within a treatment planning system (TPS) and what would otherwise be constructed by a skilled hand, thereby limiting the potential for a difference between the planned and delivered radiation dose …”
Section: Introductionmentioning
confidence: 99%
“…therapist (RT) or mould room technician, as well as variations inherent to the manual nature of the process, including air cavity flaws and imperfect contact with the patient's skin. 6,7 Three-dimensional printed bolus offers a unique solution to eliminate any physical variation between the bolus planned within a treatment planning system (TPS) and what would otherwise be constructed by a skilled hand, thereby limiting the potential for a difference between the planned and delivered radiation dose. 6,8 This study aimed to examine the volume, dimensional and dose differences between manually manufactured wax bolus and a 3D printed shell to the virtual bolus demonstrated in a radiotherapy plan for photon treatment to the nose, and to explore which type of bolus is more cost-effective to produce.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have assessed the dosimetric properties and use of rigid, solid 3D printed plastics for boluses. [9][10][11][12] The disadvantage of these materials is their lack of flexibility. Ninjaflex, however, is a lightweight, flexible material that is rigid enough to hold its shape following printing.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review by Pugh et al 9 found that the improved conformity of 3D printed bolus could prove advantageous for volumetric modulated arc therapy (VMAT) and intensity‐modulated radiotherapy (IMRT) techniques as the presence of air gaps, small field sizes, and large beam obliquity can result in a reduction of 10% in the dose at the skin surface.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of a customized bolus was proposed to increase the irregular surface dose and enhance the homogeneity of dose distribution to the tumor in the buildup region. Three-dimensional (3D) printed boluses are being increasingly applied in modern radiotherapy in recent years [4][5][6] . Thus, patient-specific boluses can be printed using the patient's surface data from imaging or other 3D surface scanning devices.…”
mentioning
confidence: 99%